2010
DOI: 10.1111/j.1365-2702.2009.03117.x
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ recovery after critical illness at early follow‐up

Abstract: Knowledge of issues in these early phases of recovery and discussion and resolution of patient problems could normalise the experience for the patient and help to facilitate better quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 48 publications
1
35
0
1
Order By: Relevance
“…In particular alterations in physical function may result from traumatic injury or debilitating effects of an illness itself, manifesting as muscle weakness, recurring pain, sleep difficulties, polyneuropathies, poor appetite, voice and taste changes all of which can reduce overall functional capacity (Needham, 2008;Richman, 2000). These observations can be supported by Kelly and McKinley's (2010) study on patients' recovery after critical illness at early followup. They have found that critical illness survivors, despite perceiving their general health as good, nevertheless experienced significant physical and psychological limitations during recovery.…”
Section: Literature Reviewsupporting
confidence: 68%
See 1 more Smart Citation
“…In particular alterations in physical function may result from traumatic injury or debilitating effects of an illness itself, manifesting as muscle weakness, recurring pain, sleep difficulties, polyneuropathies, poor appetite, voice and taste changes all of which can reduce overall functional capacity (Needham, 2008;Richman, 2000). These observations can be supported by Kelly and McKinley's (2010) study on patients' recovery after critical illness at early followup. They have found that critical illness survivors, despite perceiving their general health as good, nevertheless experienced significant physical and psychological limitations during recovery.…”
Section: Literature Reviewsupporting
confidence: 68%
“…However, the focus is on monitoring and assessing the patients' health-illness transition to ensure safety and quality care; there is no specific focus on the patients' transition experiences. This needs to be addressed because there is evidence that post-Critical Intensive Care Unit patients suffer from a variety of physical and psychological problems (Chaboyer et al, 2005;Kelly and McKinley, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Common psychological problems include anxiety, depression, post-traumatic stress disorder (PTSD) (Scragg et al, 2001), fear, and cognitive dysfunction (Kelly and McKinley, 2010;Sukantarat et al, 2005). Social problems, such as avoiding company, fear of being alone and dependence on others, have an impact on patients' social life (Griffiths and Jones, 1999).…”
Section: Implications For Clinical Practicementioning
confidence: 99%
“…Patients have physical, psychological and social problems for a long time after leaving the ICU (Broomhead and Brett, 2002). Physical problems have been described as muscle weakness, immobility, disturbed sleeping routines (Kelly and McKinley, 2010), loss of weight and change in appearance.…”
Section: Introductionmentioning
confidence: 99%
“…It is thought that the complications of a critical illness/event are not only related to the severity of the illness but also to the ICU experience [1,2]. Intensive care survivors often struggle to return to their previous role in the family and to their pre-illness state of health due to prolonged physical and neuropsychological disability [3][4][5].…”
Section: Introductionmentioning
confidence: 99%